Physical Characterization and Dissolution Study of Pentagamavunon-0 Loaded Self Nano-Emulsifying Drug Delivery System - Astuti, Ika Yuni; Marchaban, Marchaban; Martien, Ronny; Nugroho, Agung Endro (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
The recent work focuses on the physical characterization and dissolution study of PGV-0 loaded self-nanoemulsifying drug delivery system (SNEDDS). The PGV-0 SNEDDS was prepared by spontaneous emulsification method using oleic acid, tween 20:labrasol (1:1) and polyethylene glycol 400. The zeta potential of the PGV-0 SNEDDS was -34.4 ± 7.66 mv. The nanoemulsion of PGV-0 SNEDDS was thermodynamically stable with forming droplet oil containing PGV-0 in it and spherical. The dissolution result showed that the PGV-0 SNEDDS was able to increase the dissolution significantly (p <0.05) compared with PGV-0 powder of 44.13% in AGF medium and 30.37% in AIF medium. It is concluded that SNEDDS PGV-0 was able to increase the PGV-0 aqueous solubility.